ACTUAL PROBLEMS OF THE FORMATION OF SOCIAL RESPONSIBILITY OF BUSINESS IN THE REPUBLIC OF KAZAKHSTAN - Auezov Karlygash Tanatarova,; Zhanseitova Satabaeva Gulnara ,; Moldabaeva Louise Polkanova,; Maral Nabiyeva Terehanova,; Moldajanova Erkezhan Kokshenova, (Academic Journal of Physical and Chemical Sciences, 2019)
The social responsibility of business is subject to interdisciplinary research. In addition to economics, psychologists, sociologists, political scientists, etc. study various aspects of entrepreneurial activity. Government intervention in the area of social responsibility of business should be of a recommendatory, framework character. The positive Soviet experience in shaping social policy has become an example for the labor and trade union movement throughout the world. Especially important for the development of social responsibility in the country is precisely the moral support of these processes by the state - the establishment of titles, medals, prizes and certificates. Moreover, some tax breaks for corporations are even more profitable for the budget and society, since corporations are able to more accurately and efficiently solve local regional problems through social responsibility.